Harm Reduction : A New Direction for Drug Policies and Programs - O'Hare, P. A. (Patrick Anthony), 1947-; Cheung, Yuet-wah, 1952-; Riley, Diane M. (Diane Mary), 1953-; Erickson, Patricia G. (Book collections on Project MUSE., 1997)
This edited collection provides the latest in research and critical thinking on public health alternatives to conventional criminal approaches aimed at limiting the harms of both legal and illegal drugs for users and society.